Winning at risk strategies to go beyond Basel - Cortez, Annetta (Wiley finance series., 2011)
"Practical risk and capital management strategies for financial service executives and high level managers Risk and Capital Management is a primer for senior executives and directors struggling to interpret the growing demands and implications in this field. It includes valuable perspectives on how to address key issues that are pressing in the boardroom. It is the first book to lay out the basic frameworks of risk management, how to navigate new regulation, how to build a sound risk management capability, and how to translate that capability into strategic success. A must-have management aid and reference tool for the financial services professional Expert coverage of measuring risk, managing risk, integrating risk management into business, and leveraging business excellence through risk Written by a respected thought leader in risk management Providing CEOs and financial executives with the basic building blocks and concepts of risk management, this essential book simplifies risk management requirements for board and executive level professionals"--